Adapting the Principle of Sadd al-Zari’ah by the Government in the Regulation of Product and Service Labelling - Suraiya Osman; Yasmin Hanani Mohd Safian (School of Muamalat and Management, Kolej Pengajian Islam Johor (MARSAH), 2024)
Non-Indexed Publication